ANALISIS PERAN KELUARGA DALAM MEMBINA KARAKTER ANAK - Fidya Zafirah Harakah Islami; Sumardi; Nita Karmila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study uses a qualitative approach with a case study method that aims to determine the role of the family in fostering children's character and to find out what factors can foster child character. The subjects in this study were children aged 10 years who were still in elementary school. Data was collected through observation, interviews and documentation studies. The results showed that children have good character for their age. Through the role of the family that is carried out from an early age, children grow up to have the character of responsibility, independence, and interest. Often families provide examples and show examples to children, indirectly children follow and apply them. Not only that, children also have several achievements in the field of Al-Qur'an hafidz and Taekwondo Championships throughout the Province. Based on the results of these studies, it can be concluded that the family has a role in fostering the character of children.